Using Interactive Language Development Tools to Enhance Cognitive and Literacy Skills in K-12 Education - Maspul, Kurniawan Arif (UIR Press, 2024)
The incorporation of interactive language technologies, such as ChatGPT, into K-12 education has sparked interest as a way to improve language acquisition and cognitive development. This qualitative study investigates the perspectives and experiences of educators enrolled in the Advanced Teaching MEd program who have implemented ChatGPT in their language classes. The study investigates the influence of ChatGPT on language competence, cognitive skills, and literacy development using educator interviews, classroom observations, and a comprehensive literature analysis. The findings underscore ChatGPT's dynamic and interactive nature, which encourages active involvement, knowledge production, and tailored support in the zone of proximal growth. Furthermore, the study demonstrates how ChatGPT improves language proficiency by offering authentic language experiences, timely feedback, and exposure to a variety of linguistic structures. ChatGPT integration helps students become confident communicators and teachers construct dynamic classes that adapt to specific learning needs. Future research should look at the long-term impact of interactive language tools, the importance of teacher training, and the cultural and socioeconomic aspects that influence their use and efficacy. This work adds to the continuing efforts to improve language learning outcomes in K-12 education by increasing our understanding of how interactive language tools can boost cognitive development and language competency.